Lactobacillus pentosus strain S-PT84 improves steatohepatitis by maintaining gut permeability. Issue 2 (November 2020) - Sakai, Yuriko; Arie, Hideyuki; Ni, Yinhua; Zhuge, Fen; Xu, Liang; Chen, Guanliang; Nagata, Naoto; Suzuki, Takuya; Kaneko, Shuichi; Ota, Tsuguhito; Nagashimada, Mayumi
Abstract : Intestinal mucosal barrier dysfunction is closely related to the pathogenesis of nonalcoholic steatohepatitis (NASH). Gut immunity has been recently demonstrated to regulate gut barrier function. The Lactobacillus pentosus strain S-PT84 activates helper T cells and natural killer/natural killer T cells. In this study, we examined the effect of S-PT84 on NASH progression induced by high-cholesterol/high-fat diet (CL), focusing on the immune responses involved in gut barrier function. C57BL/6 mice were fed a normal chow or CL diet with or without 1 × 10 10 S-PT84 for 22 weeks. S-PT84 administration improved hepatic steatosis by decreasing triglyceride and free fatty acid levels by 34% and 37%, respectively. Furthermore, S-PT84 inhibited the development of hepatic inflammation and fibrosis, suppressed F4/80 + macrophage/Kupffer cell infiltration, and reduced liver hydroxyproline content. Administration of S-PT84 alleviated hyperinsulinemia and enhanced hepatic insulin signalling. Compared with mice fed CL diet, mice fed CL+S-PT84 had 71% more CD11c - CD206 + M2 macrophages, resulting in a significantly decreased M1/M2 macrophage ratio in the liver. Moreover, S-PT84 inhibited the CL diet-mediated increase in intestinal permeability. Additionally, S-PT84 reduced the recruitment of interleukin-17-producing T cells and increased the levels of intestinal tight junction proteins, including zonula occludens-1, occludin, claudin-3, and claudin-7. In conclusion, our findings suggest that S-PT84 attenuates diet-induced insulin resistance and subsequent NASH development by maintaining gut permeability. Thus, S-PT84 represents a feasible approach to prevent the development of NASH.